Antimicrobial activity of Rhus coriaria L. fruit extracts against selected bacterial and fungal pathogens on tomato - Rashid, Tavga Sulaiman (2016)
An effective and efficient nanoemulsion biopesticide derived from Rhus coriaria was developed for the control of selected tomato bacterial and fungal pathogens. Fruit extracts of Rhus coriaria were screened for antifungal and antibacterial activities in vitro and extract that showed strongest activity was screened in vivo. Aqueous, methanol, acetone and ethanol extracts of R. coriaria resulted in the production of antifungal and antibacterial substances that significantly inhibited the growth of Rhizoctonia solani, Fusarium oxysporum, Fusarium solani, Fusarium acuminatum,Phoma destructiva, Colletotrichum acutatum and Colletotrichum boninense and three selected bacterial pathogens Pseudomonas syringae, Ralstonia solanacearum and Xanthomonas vesicatoria (P˂0.05). The best inhibitory effect was elicited by aqueous extract against C. bonininse and C. acutatum (82.3% radial growth inhibition), while crude ethanol extract showed the least significant effect 61.62%. Aqueous extract showed the best inhibitory effect against X. vesicatoria the inhibition zone was 30mm followed by P. syringae and R. solanacearum (26.5 and 23.5 mm respectively). The result showed that R. coriaria fruit extract has inhibitory effect on all types of fungi and bacteria. Light and scanning electron microscopic observations showed that active crude extract resulted in degraded, twisted, shriveled, burst and with distorted morphology of fungal cell wall and bacterial cells. The aqueous crude extract was further purified through High Performance Liquid Chromatography (HPLC) fractionation and resulted in the total of 55 fractions. Results showed that most of the fractions have antibacterial activity where the inhibition zones were between 31.6- 17.3mm, while only nine fractions showed antifungal activity of 75-65 %. Antimicrobial effects of the most effective extract of R. coriaria crude extract was supported by the presence of chemical constituents identified by GC-MS. Furfural, 2,5-Furandione, 1-Cyclopetene, Phloroglucinol, Succinic acid, p-Tolylacetic acid, Malic acid and Coumalic acid were detected as major compounds in R. coriaria fruit extract that were possibly responsible for the antimicrobial activity. The non-volatile compounds present were identified by Liquid chromatography–mass spectrometry (LC-MS). Gallic acid, gallic acid conjugate, tannic acid, phenylvaleric acid, quercetin conjugate, malic acid, 2(3,4-ihydroxyphenyl)-7-hydroxy-5-benzenepropanoic acid,and 3,30-di-O-methyl ellagic acid conjugate were detected as major compounds in aqueous fruit extract that were possibly responsible for antimicrobial activities . From the five surfactants used Emereen 1820 showed to be the best surfactant and was stable after six months of storage. A surface tension value of nanoemulsion solution was 27.174 mN/m, while particle size was 70.44 nm. The formulation was evaluated for its efficacy in controlling two of the most destructive fungi and two common bacteria under glasshouse condition. Overall, the nano-emulsion formulation showed strong activity in reducing disease incidence and the disease reduction was between (82.58- 64.80%) at the concentration 10% w/w while reduction was between (66.43-54.07%) at the concentration 5%, in comparison with antibiotic and fungicide. Nano-emulsion formulation was able to increase significantly shoot height (45%), root length (33%),shoot height dry weight (65%) and root dry weight (59.3%) compared to the positive and negative control at the 8th weeks of plant growth.